Disella ilicicola population fluctuation in Paraguay tea orchard - Chiaradia, Luís Antônio; Milanez, José Maria; Nesi, Cristiano Nunes (Revista de Ciências Agroveterinárias, 2006)
The small mite Disella ilicicola Navia e Flechtmann (Acari: Eriophyidae) causes chlorosis in leaves of Paraguay tea (Ilex paraguariensis St. Hil., Aqüifoliaceae). Population fluctuation of this pest was studied from July of 2003 to June of 2006 in an orchard situated in Chapecó, Santa Catarina State, Brazil. Samplings were carried out every two weeks registering the number of mite observed on under face areas of 1cm2 of three leaves of 20 trees using lenses with ten times increase. Linear correlation analysis was applied between the pest and the predator mite Agistemus brasiliensis Matioli et al. (Acari: Stigmaeidae) and with climatic factors. Correlation coefficients between climatic factors and the pest were not significant. Components main analysis between the variables showed strong positive correlation between D. ilicicola and the predator mite (r = 0.88 and P < 0.01), moderate negative correlation between the pest and the wind speed and moderate positive correlation between the phytophago mite and the average temperature.